Stress and Coping Among Health Professions Students During COVID-19: A Perspective on the Benefits of Mindfulness - Luberto, Christina M (Glob Adv Health Med, 2020)
Many health professions students experience elevated stress and burnout during their professional education and training. With the added challenges of COVID-19, students face a whole new set of stressors. Students in the Spring 2020 semester of our online academic course, “Mindfulness for Healthcare Providers,” began confronting the COVID-19 crisis after several weeks of mindfulness meditation practice as part of the course. Students discussed their experiences using the course discussion boards, providing a unique opportunity to explore the practical application of mindfulness for student well-being during a crisis. Themes from the discussion board revealed a range of novel stressors and concerns due to COVID-19 (physical health, mental health, societal implications, academic and clinical training disruptions). All students reported that mindfulness practice helped them cope by improving specific mindfulness skills (focus, appreciation, cognitive de-centering, non-reactivity). Mindfulness training may be a useful approach to promoting student well-being during a crisis.